2014
DOI: 10.4028/www.scientific.net/amr.1054.177
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mixed Ceramic Powder in Cement Based Composites

Abstract: Waste ceramic powder coming from grinding the ceramic bricks disposed on demolition depot is investigated as partial Portland cement replacement in blended binders. For the milled ceramic powder, measurement of specific surface area (SSA) and particles size distribution is done. Its chemical composition is accessed using X-Ray Fluorescence (XRF) and X-Ray Diffraction (XRD) analysis. The blended binders containing ceramic powder in an amount of 8, 16, 24, 32, and 40% of mass of cement are used for the preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Therefore, the chemical reactions between SiO 2 and Ca(OH) 2 resulted in the formation of additional C-S-H gels in the ceramic mortar [20]. Through the development of additional C-S-H gels, the porosity reduced and consequently resulted in higher strength of mortar at longer curing periods [21].…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Therefore, the chemical reactions between SiO 2 and Ca(OH) 2 resulted in the formation of additional C-S-H gels in the ceramic mortar [20]. Through the development of additional C-S-H gels, the porosity reduced and consequently resulted in higher strength of mortar at longer curing periods [21].…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Regarding the specific application of ceramic waste as a pozzolan material to act as OPC for structural concrete, Table 1 presents main works on this subject. A wide variation in the type of waste and related composition are highlighted in these works [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Irassar et al [ 35 ] investigated an Argentinean industrial waste mostly of quartz, 51.3% SiO 2 , 20% Al 2 O 3 and 11.5% CaO and feldspar, anorthite and hematite. Pokorný et al [ 36 ] evaluated the pozzolanic potential of Spanish industrial ceramic block waste, which was characterized by an elevate content of gypsite, 37% SiO 2 , 14.3% Al 2 O 3 , 15.2% CaO and 17.9% SO 3 , in addition to microcline, albite and muscovite. With similar work as in [ 35 ], Vejmelková et al [ 37 ] used thermal insulation block waste.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of CWP as partial replacement of cement attracted the attention of several researchers [6,[23][24][25][26][27][28][29][30][31][32][33][34][35]. The main conclusion from the studies was that CWP showed slow pozzolanic activity which was evidenced at late ages.…”
Section: Introductionmentioning
confidence: 99%